2013
DOI: 10.2169/internalmedicine.52.9073
|View full text |Cite
|
Sign up to set email alerts
|

An Elevated Ratio of Placental Growth Factor to Soluble Fms-like Tyrosine Kinase-1 Predicts Adverse Outcomes in Patients with Stable Coronary Artery Disease

Abstract: Objective To investigate the predictive values of placental growth factor (PlGF) and its endogenous antagonist, soluble fms-like tyrosine kinase-1 (sFlt-1), for the long-term prognosis of patients with stable coronary artery disease (CAD). Both PlGF and sFlt-1 play important roles in the pathological mechanisms of atherosclerosis. We recently demonstrated that the plasma levels of these molecules are correlated with the severity of coronary atherosclerosis. Methods We enrolled 464 patients with stable CAD who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
2
16
1
Order By: Relevance
“…An association between PlGF and NYHA classes was previously documented [26]. A previous report also showed that sFlt-1 was independently associated with HF severity and natriuretic peptides [13]. Furthermore, the combined assessment of sFlt-1 and BNP in the present study yielded higher predictive accuracy with adverse outcomes [13].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…An association between PlGF and NYHA classes was previously documented [26]. A previous report also showed that sFlt-1 was independently associated with HF severity and natriuretic peptides [13]. Furthermore, the combined assessment of sFlt-1 and BNP in the present study yielded higher predictive accuracy with adverse outcomes [13].…”
Section: Discussionsupporting
confidence: 73%
“…Beside preeclampsia, PlGF was demonstrated to contribute to the development of coronary atherosclerosis, by enhancing intramural angiogenesis and promoting inflammatory monocytes and macrophages migration into the arterial wall [12]. It was also recently reported that circulating levels of sFlt-1 and PlGF are elevated in patients with advanced coronary atherosclerosis and HF [13,14]. A paracrine role of sFlt-1 and PlGF as regulators of cardiac adaptation and hypertrophy was also suggested [8,9].…”
Section: Introductionmentioning
confidence: 97%
“…9.4 (9.0-9.7) 9.3 (9.0-9.6) 9.3 (8.9-9.5) 9.3 (9.0-9.7) 0.01 Recently, a growing body of clinical evidence suggests that PlGF alone or in combination with other biomarkers is a powerful predictor of survival or cardiovascular events in patients with stable and unstable coronary artery disease [17][18][19][20]24 ; however, some studies have not demonstrated that PlGF is independently associated with survival in patients with chronic heart failure or suspected acute myocardial infarction. 22,23 More recently, a single-center study showed that elevated PlGF level is an independent predictor of increased mortality but not cardiovascular events in patients with…”
Section: Discussionmentioning
confidence: 99%
“…It binds PlGF and VEGF and acts as a decoy receptor, inhibiting the effects of both PlGF and VEGF. PlGF and sFlt-1 have emerged as practical clinical predictors of mortality and cardiovascular disease in patients with chronic heart failure, ischemic heart disease, diabetes, and CKD [5,12,18,19,20,21]. In addition, as shown by Guo et al [10], sFlt-1 is independently associated with all-cause mortality in HD patients; however, the association between PlGF and adverse outcomes has not yet been investigated in PD patients.…”
Section: Discussionmentioning
confidence: 99%